Low-temperature-coefficient copper paste for high-power device and manufacturing method of low-temperature-coefficient copper paste

By using copper powder with high spherical and high tap density and adding nano-scale negative temperature coefficient metal oxide materials, the existing copper slurry has been solved, significantly reducing the temperature coefficient of the device, and improving reliability and thermal resistance performance.

CN119626623APending Publication Date: 2025-03-14CHINA ZHENHUA GRP YUNKE ELECTRONICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411832500.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing copper slurry has a high temperature coefficient, and the accumulated thermal effect of the device is significant under high-power operating conditions, resulting in device failure and reduced reliability.

Method used

Copper powder with high spherical and high tap density is used, and a nano-scale negative temperature coefficient metal oxide material is added to form a chimeric three-dimensional Internet-like electrical link to reduce the positive temperature coefficient of the copper slurry sintered film layer.

Benefits of technology

The temperature coefficient of the copper slurry sintered film layer is significantly reduced, from 3930ppm/℃ to ±500ppm/℃, improving the reliability and thermal resistance of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119626623A_ABST
    Figure CN119626623A_ABST
Patent Text Reader

Abstract

The invention discloses low-temperature-coefficient copper paste for a high-power device and a manufacturing method thereof, and belongs to the field of electronic paste. The copper paste comprises the following components in percentage by weight: 40wt%-80wt% of copper powder, 0.5 wt%-10wt% of glass powder, 0.05 wt%-5wt% of oxide additive and 15wt%-50wt% of organic carrier, wherein the organic carrier comprises organic resin and an organic solvent. The preparation method comprises the following steps: weighing the components, uniformly mixing the components, and grinding until the average particle size of the copper powder is D50 (0.5-20 microns), the fineness of the tested slurry is less than or equal to 30 microns, and the viscosity range is 80-300 Pa.s, thereby obtaining the copper slurry of the corresponding embodiment. The problems that the temperature coefficient of existing copper paste is high, the accumulated heat effect of a device is remarkably increased under the high-power working condition, the device loses efficacy, and the reliability is reduced are solved. The method is widely applied to the technical field of wiring of low-thermal-resistance high-power component substrates and high-current wires.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of electronic paste, and further relates to the field of metal paste, and specifically, to a low temperature coefficient copper paste for high-power devices and a preparation method thereof. Background Art

[0002] In recent years, with the rapid development of copper-based LTCC materials and preparation technologies, the market for passive electronic components with excellent electrical and mechanical properties such as high strength, high airtightness, high thermal conductivity, high frequency, high speed transmission, wide bandwidth, low dielectric constant, low loss and low cost has developed rapidly and is widely used in wireless communications, consumer electronics, automotive electronics, aerospace and other fields.

[0003] With the continuous iteration and upgrading of microelectronics technology, the demand side has put forward more stringent requirements for the integration, miniaturization, high power, low power consumption, high reliability and other performance of passive electronic components. It is required that the copper paste supporting the LTCC material not only needs to match the raw ceramic material for co-firing and sintering the film layer with high conductivity, but also needs to have extremely low Joule heating effect under large temperature conditions. However, under high-power and high-integration working conditions, the internal conductor of the high-power LTCC device generates large Joule heat energy. Due to the high temperature coefficient of the existing copper paste, the device resistance rises rapidly under high-power working conditions, resulting in significant cumulative thermal effects, which easily generates thermal stress and causes device structure failure. Therefore, how to reduce the positive temperature coefficient effect of the copper paste sintering film layer has become an urgent issue.

[0004] At present, the most widely studied method for reducing the temperature coefficient of the copper paste sintered film layer at home and abroad is to achieve a high sintering density of the copper paste sintered film layer by combining nano-scale, micron-scale spherical or flaky copper powder, low sintering temperature glass powder, etc., to improve the overall conductivity of the device, thereby reducing the initial thermal effect of the device; due to the unilateral increase in the density of the copper paste sintered film layer and the reduction of sintered film defects, the square resistance of the copper paste sintered film layer can only be reduced from a single dimension to be infinitely close to the theoretical square resistance of copper element, and the basic physical and chemical properties of the copper material are not changed. Among them, the improvement of the density of the copper paste sintered film layer can significantly improve the conductivity of the sintered film layer to be close to the theoretical conductivity of 1.68×10-6Ω·cm, but the temperature coefficient of the copper material is as high as 3930ppm / ℃. During the operation of high-power devices, significant cumulative thermal effects will still occur, thereby reducing the reliability of the device.

[0005] Therefore, in order to further develop copper paste with inherent high conductivity and low temperature coefficient, the present invention is proposed. Summary of the invention

[0006] The technical problem to be solved by the present invention is to solve the problem that the temperature coefficient of the existing copper paste is high, the cumulative thermal effect of the device is significantly increased under high-power working conditions, resulting in device failure and reduced reliability.

[0007] The object of the present invention is to reduce the positive temperature coefficient effect of the copper paste sintered film layer, so that the thermal resistance of the copper paste sintered film layer increases significantly with increasing temperature.

[0008] To this end, the present invention provides a low temperature coefficient copper paste for high-power devices, the components of which include, by weight percentage: 40wt% to 80wt% of copper powder, 0.5wt% to 10wt% of glass powder, 0.05wt% to 5wt% of oxide additives, and 15wt% to 50wt% of organic carrier.

[0009] The copper powder has an average particle size D50 of 0.5 μm to 20 μm, a sphericity of 0.85 to 0.989, and a tap density of 3.53 g / cm3 to 6.7 g / cm3.

[0010] The average particle size D50 of the glass powder is 0.5 μm to 15 μm, and the sintering temperature is 800° C. to 980° C.

[0011] The average particle size D50 of the oxide additive is 10nm to 500nm.

[0012] The organic carrier includes organic resin and organic solvent.

[0013] The method for preparing the low temperature coefficient copper paste for high-power devices is as follows: Weighing: Weigh according to the specified components; Mixing: uniformly dispersing the weighed solid particles consisting of copper powder, glass powder and oxide additive in the organic carrier to obtain a sample slurry; Grinding: Use a grinder to grind the sample slurry into copper slurry. The average particle size of the copper powder is D50 (0.5μm~20μm); Test: When the slurry fineness is ≤30 μm and the viscosity ranges from 80 Pa·s to 300 Pa·s, the copper slurry of the corresponding embodiment is prepared.

[0014] The sintering method of the low temperature coefficient copper paste for high-power devices is as follows: The LTCC substrate printed with copper paste is placed in a sintering furnace with a sintering temperature of 850℃~1000℃ and kept at the peak temperature for 10min~120min to form a copper sintering film layer. The sheet resistance of the copper sintering film layer is 0.5mΩ / □~20mΩ / □, and the temperature coefficient is within ±500ppm / ℃ (-55℃~125℃).

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1) The copper powder with high sphericity and high tap density used in the present invention is beneficial to improve the density of the copper sintered film layer and obtain low square resistance and high conductivity; 2) In the present invention, by adding one or more nano-scale negative temperature coefficient metal oxide materials, after the copper paste is sintered, it can form an embedded three-dimensional internet-like electrical link with the copper film layer, forming a copper and negative temperature coefficient metal oxide series / parallel complex structure, and reducing the temperature coefficient of the copper sintered film layer itself from 3930ppm / ℃ to ±500ppm / ℃. The test temperature range is -55℃~125℃, with a low temperature coefficient.

[0016] The low temperature coefficient copper paste can be widely used in the fields of low thermal resistance high power component substrates and high current wire wiring technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a SEM schematic diagram of the surface morphology of the sintered film layer of Example 1 of the present invention. DETAILED DESCRIPTION

[0018] like Figure 1 As shown, the low temperature coefficient copper paste for high-power devices and the sintering method thereof are specifically implemented as follows: The oxide additive can be selected from one or more of lanthanum oxide, cerium oxide, neodymium oxide, samarium oxide, praseodymium oxide, gadolinium oxide, manganese oxide, cobalt oxide, aluminum oxide, calcium oxide, strontium oxide, barium oxide, iron oxide, nickel oxide, tantalum oxide, and titanium oxide.

[0019] The organic resin may be selected from one or more of cellulose acetate, cellulose nitrate, and acrylic acid.

[0020] The organic solvent may be selected from one or more of lauryl alcohol ester, triacetin, and butyl acetate. Embodiment 1:

[0021] The components of the low temperature coefficient copper paste are: 75 parts of copper powder, 0.8 parts of glass powder, 0.03 parts of manganese oxide additive and 0.05 parts of aluminum oxide additive, and 24.12 parts of organic carrier. Embodiment 2:

[0022] The components of the low temperature coefficient copper paste are: 75 parts of copper powder, 0.8 parts of glass powder, 0.04 parts of nickel oxide additive and 0.04 parts of tantalum oxide additive, and 24.12 parts of organic carrier. Embodiment 3:

[0023] The components of the low temperature coefficient copper paste are: 65 parts of copper powder, 0.5 parts of glass powder, 0.03 parts of manganese oxide additive and 0.05 parts of aluminum oxide additive, and 34.42 parts of organic carrier. Embodiment 4:

[0024] The components of the low temperature coefficient copper paste are: 75 parts of copper powder, 0.8 parts of glass powder, 1.0 parts of lanthanum oxide additive, and 23.2 parts of organic carrier. Embodiment 5:

[0025] The components of the low temperature coefficient copper paste are: 80 parts of copper powder, 2.0 parts of glass powder, 0.5 parts of cobalt oxide and 0.2 parts of manganese oxide additives, and 17.3 parts of organic carrier.

[0026] Comparative Example 1: The composition of a copper paste for high-power devices is: 75 parts of copper powder, 0.8 parts of glass powder, and 24.2 parts of organic carrier, that is, no oxide additives.

[0027] The copper paste preparation methods of Examples 1-5 and Comparative Example 1 are as follows: Weighing: Weigh according to the specified components; Mixing: The weighed components are fully mixed with a paddle-type powder mixer for 10 to 30 minutes, and then the mixed powder is mixed with the weighed organic carrier with a scraper to obtain a sample slurry; Grinding: Grind the sample slurry 40 times using a three-roll grinder, gradually reducing the distance between the inlet and outlet rollers of the three-roll grinder until the roller distance is approximately equal to the average particle size D50 (0.5 μm to 20 μm) of the copper powder in the copper slurry; Test: When the slurry fineness is ≤30 μm and the viscosity ranges from 80 Pa·s to 300 Pa·s, the copper slurry of the corresponding embodiment is prepared.

[0028] For the copper pastes of Examples 1-5 and Comparative Example 1, under the same manufacturing method and sintering method, the test data of the sheet resistance and temperature coefficient of the corresponding copper sintered film layers are shown in Table 1.

[0029] Table 1 Comparison of the square resistance and temperature coefficient test data of Examples 1-5 and Comparative Example 1 Example Square resistance (mΩ / □) Temperature coefficient (ppm / ℃) Example 1 3.4 241 Example 2 3.54 103 Example 3 3.8 383 Example 4 4.1 350 Example 5 3.7 -277 Comparative Example 1 3.4 3770 It can be seen from Table 1 that, compared with Comparative Example 1, the temperature coefficients of the copper pastes of Examples 1 to 5 fluctuate within approximately ±350, while the temperature coefficient of the copper paste of Comparative Example 1, which lacks oxide additives, rises significantly, by more than 10 times, indicating that the effect improvement of the present invention is quite prominent and obvious.

[0030] In particular, under the sintering conditions of a copper paste sintering temperature of 950°C and a holding time of 60 min, the average square resistance of the copper sintered film layer is 3.54 mΩ / □, and the average temperature coefficient is 103 ppm / °C.

[0031] Finally, it should be noted that the above embodiments are merely examples for the purpose of clear explanation. The present invention includes but is not limited to the above embodiments. It is not necessary and impossible to list all implementation methods exhaustively. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. All implementation methods that meet the requirements of the present invention belong to the protection scope of the present invention.

Claims

1. A low temperature coefficient copper paste for high power devices, characterized in that: By weight percentage, the components include: 40wt% to 80wt% of copper powder, 0.5wt% to 10wt% of glass powder, 0.05wt% to 5wt% of oxide additive, and 15wt% to 50wt% of organic carrier; The copper powder has an average particle size D50 of 0.5 μm to 20 μm, a sphericity of 0.85 to 0.989, and a tap density of 3.53 g / cm3 to 6.7 g / cm3; The average particle size D50 of the glass powder is 0.5 μm to 15 μm, and the sintering temperature is 800° C. to 980° C.; The average particle size D50 of the oxide additive is 10nm to 500nm; The organic vehicle includes an organic resin and an organic solvent.

2. The low temperature coefficient copper paste for high power devices according to claim 1, characterized in that: The oxide additive is one or more of lanthanum oxide, cerium oxide, neodymium oxide, samarium oxide, praseodymium oxide, gadolinium oxide, manganese oxide, cobalt oxide, aluminum oxide, calcium oxide, strontium oxide, barium oxide, iron oxide, nickel oxide, tantalum oxide, and titanium oxide.

3. The low temperature coefficient copper paste for high power devices according to claim 1, characterized in that: The organic resin is one or more of cellulose acetate, cellulose nitrate, and acrylic acid; The organic solvent is one or more of lauryl alcohol ester, triglycerol acetate, and butyl acetate.

4. The low temperature coefficient copper paste for high power devices according to claim 1, characterized in that: The components of the low temperature coefficient copper paste are: 75 parts of copper powder, 0.8 parts of glass powder, 0.03 parts of manganese oxide additive and 0.05 parts of aluminum oxide additive, 24.12 parts of organic vehicle.

5. The low temperature coefficient copper paste for high power devices according to claim 1, characterized in that: The components of the low temperature coefficient copper paste are: 75 parts of copper powder, 0.8 parts of glass powder, 0.04 parts of nickel oxide additive and 0.04 parts of tantalum oxide additive, 24.12 parts of organic vehicle; Or 65 parts of copper powder, 0.5 parts of glass powder, 0.03 parts of manganese oxide additive and 0.05 parts of aluminum oxide additive, 34.42 parts of organic carrier.

6. The low temperature coefficient copper paste for high power devices according to claim 1, characterized in that: The components of the low temperature coefficient copper paste are: 75 parts of copper powder, 0.8 parts of glass powder, 1.0 parts of lanthanum oxide additive, 23.2 parts of organic carrier; Or 80 parts of copper powder, 2.0 parts of glass powder, 0.5 parts of cobalt oxide and 0.2 parts of manganese oxide additives, and 17.3 parts of organic carrier.

7. The sintering method of a low temperature coefficient copper paste for high power devices according to claim 1, characterized in that: The production method is as follows: Weighing: Weigh according to the specified components; Mixing: uniformly dispersing the weighed solid particles consisting of copper powder, glass powder and oxide additive in the organic carrier to obtain a sample slurry; Grinding: Use a grinder to grind the sample slurry into copper slurry. The average particle size of the copper powder is D50 (0.5μm~20μm); Test: When the slurry fineness is ≤30 μm and the viscosity ranges from 80 Pa·s to 300 Pa·s, the copper slurry of the corresponding embodiment is prepared.

8. The sintering method of a low temperature coefficient copper paste for high power devices as claimed in claim 7, characterized in that: The specific production method is as follows: Weighing: Weigh according to the specified components; Mixing: The weighed components are fully mixed with a paddle-type powder mixer for 10 to 30 minutes, and then the mixed powder is mixed with the weighed organic carrier with a scraper to obtain a sample slurry; Grinding: Grind the sample slurry 40 times using a three-roll grinder, gradually reducing the distance between the inlet and outlet rollers of the three-roll grinder until the roller distance is approximately equal to the average particle size D50 (0.5 μm to 20 μm) of the copper powder in the copper slurry; Test: When the slurry fineness is ≤30 μm and the viscosity ranges from 80 Pa·s to 300 Pa·s, the copper slurry of the corresponding embodiment is prepared.

9. The sintering method of a low temperature coefficient copper paste for high power devices according to claim 1, characterized in that: The sintering method of low temperature coefficient copper paste is as follows: The LTCC substrate printed with copper paste is placed in a sintering furnace with a sintering temperature of 850°C to 1000°C, and kept at the peak temperature for 10min to 120min to form a copper sintered film layer; the square resistance of the copper sintered film layer is 0.5mΩ / □ to 20mΩ / □, and the temperature coefficient in the range of -55°C to 125°C is within ±500ppm / ℃.

10. The sintering method of a low temperature coefficient copper paste for high power devices according to claim 9, characterized in that: Under the sintering conditions of copper paste sintering temperature of 950℃ and holding time of 60min, the average square resistance of the copper sintered film layer is 3.54mΩ / □ and the average temperature coefficient is 103ppm / ℃.